Nonlegumes Respond to Rhizobial Nod Factors by Suppressing the Innate Immune Response - Liang, Yan; Cao, Yangrong; Tanaka, Kiwamu; Thibivilliers, Sandra; Wan, Jinrong; Choi, Jeongmin; ho Kang, Chang; Qiu, Jing; Stacey, Gary (Science (American Association for the Advancement of Science), 2013)
Virtually since the discovery of nitrogen-fixing Rhizobium-legume symbioses, researchers have dreamed of transferring this capability into nonlegume crop species (for example, corn). In general, nonlegumes were assumed to lack the ability to respond to the rhizobial lipo-chitin Nod factors, which are the essential signal molecules that trigger legume nodulation. However, our data indicate that Arabidopsis thaliana plants, as well as other nonlegumes, recognize the rhizobial Nod factor via a mechanism that results in strong suppression of microbe-associated molecular pattern (MAMP)—triggered immunity. The mechanism of action leads to reduced levels of pattern-recognition receptors on the plasma membrane involved in MAMP recognition.